1988
DOI: 10.1111/j.2044-8279.1988.tb00888.x
|View full text |Cite
|
Sign up to set email alerts
|

Learned Helplessness, Self‐worth Motivation and Attribution Retraining for Primary School Children

Abstract: This study examined characteristics of 29 pupils (selected from an initial sample of 69 primary school children) whose performance on an arithmetic task deteriorated after failure. On the basis of their responses to a "mitigating circumstance" which could explain failure without implicating low ability as the cause (a description of the task as "very difficult"), subjects were classified as either learned helpless or motivated to protect self-worth. Both of these groups had lower self-concepts than the rest of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
1
3

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 18 publications
5
57
1
3
Order By: Relevance
“…There is evidence from Volet's (1999) study on the performance of South East Asian students, that the situation might indeed be different. Furthermore, contrary to early reports (Dweck, 1975;Craske, 1988) which were unable to establish any conclusive link between gender and motivational styles, recent studies (Koh & Galloway, 2006) showed a higher proportion of maladaptive males as compared to females. These findings thus serve to highlight the role of context and culture in influencing motivational patterns amongst individuals.…”
Section: Defining Motivational Stylesmentioning
confidence: 47%
See 4 more Smart Citations
“…There is evidence from Volet's (1999) study on the performance of South East Asian students, that the situation might indeed be different. Furthermore, contrary to early reports (Dweck, 1975;Craske, 1988) which were unable to establish any conclusive link between gender and motivational styles, recent studies (Koh & Galloway, 2006) showed a higher proportion of maladaptive males as compared to females. These findings thus serve to highlight the role of context and culture in influencing motivational patterns amongst individuals.…”
Section: Defining Motivational Stylesmentioning
confidence: 47%
“…First, it was necessary to identify the motivational styles (mastery orientation, selfworth motive or learned-helplessness) of the students involved. This was carried out using an adaptation of the procedure devised by Craske (1988) in which the performance of the students in a series of four subject matter tests was used to identify their motivational styles. Secondly, once the students' motivational styles were known, it was then possible to conduct the intervention procedure, attribution retraining, and to assess its effect on students identified as maladaptive (self-worth motivated and learnedhelpless).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations